Multifunctional Thiosemicarbazones and Deconstructed Analogues as a Strategy to Study the Involvement of Metal Chelation, Sigma-2 (σ(2)) Receptor and P-gp Protein in the Cytotoxic Action: in vitro and in vivo Activity in Pancreatic Tumors - Pati, Maria Laura (Eur J Med Chem, 2017)
The aggressiveness of pancreatic cancer urgently requires more efficient treatment options. Because the sigma-2 (σ(2)) receptor was recently proposed as a promising target for pancreatic cancer therapy, we explored our previously developed multifunctional thiosemicarbazones, designed to synergistically impair cell energy levels, by targeting σ(2) and P-gp proteins and chelating Iron. A deconstruction approach was herein applied by removing one function at a time from the potent multifunctional thiosemicarbazones 1 and 2, to investigate the contribution to cytotoxicity of each target involved. The results from in vitro (panel of pancreatic tumor cells) and in vivo experiments (C57BL/6 bearing KP02 tumor), suggest that while the multifunctional activity was not required for the antitumor activity of these thiosemicarbazones, σ(2)-targeting appeared to allow alternative tumor cell death mechanisms, leading to potent and less toxic off-targets toxicities compared to other thiosemicarbazones devoid of σ(2)-targeting.